Physiology of body lateralization on regional lung ventilation and lung volumes in healthy subjects: Within-subjects design - Layane S. P. Costa; Cyda M. A. Reinaux; Emanuel F. F. Silva Júnior; Wagner S. Leite; Daniella C. Brandão; Armèle Dornelas de Andrade; Rollin Roldán; Caio C. A. Morais; Shirley Lima Campos (PLoS ONE, 2025)
Introduction Lateral positioning improves pulmonary mechanics and lung volumes, but its effects in healthy adults remain unclear due to individual variability. Objective To analyze the acute effects of lateral body positioning on regional lung ventilation and lung volumes in healthy adults. Methods This within-subject study included two protocols: supine and left-lateral position (unilateral) with repeated measures and supine, left, and right-lateral positions (bilateral). All positions were performed at 30° for 5 minutes on an automated rotation bed. Electrical Impedance Tomography measured regional lung ventilation (%) and end-expiratory lung volumes (EELV) across four lung regions: (anterior right [AR] and left [AL]; posterior right [PR], and left [PL]). Linear mixed models assessed the influence of body position and individual variability on regional ventilation and lung volumes, while the Restricted Maximum Likelihood method compared between right- and left-lateral positioning. Results In the unilateral protocol (n = 29; 58.6% male; 22.8 ± 4.0 years), left-lateral positioning decreased regional ventilation in nondependent regions (AR: −0.96%, PR: −1.63%) and increased it in dependent regions (PL: 1.17%, AL: 1.42%) versus supine (p < 0.001). EELV increased in PL (+ 0.7 mL/kg PBW), PR (+2.0), and AR (+2.8), but decreased in AL (−2.3) ( p < 0.001). In the bilateral protocol (n = 10, 70% male; 23.6 ± 3.2 years), regional ventilation showed no significant effects of position, ROI, or interaction ( p > 0.05). However, EELV varied significantly with body position ( p < 0.001), with no isolated ROI effect ( p = 1.000). Conclusions Lateral positioning improves regional ventilation in dependent lung regions and increases EELV in nondependent and posterior dependent lung regions, regardless of side. Trial registration ClinicalTrials.gov [ NCT06044896 ]